The problems of data delivery in networks with insensitivity to delays - Лукашенко, В. В. (Problems of Informatization and Control, 2012)
The task of organizing the processes of delivering messages in networks with insensitivity to delivery delays and breaks the connection between network nodes (DTN-networks). Simulated the process of delivering messages to mobile DTN-network. Given the comparative quantitative estimates of the parameters of reliability of delivery depending on the number of replicated messages